Report on Improved Agricultural Implements (Punjab) - Planning Commission (Planning Commission, Government of India, 1963)
The Report on Improved Agricultural Implements (Punjab), August 1963 examines the challenges and opportunities in modernizing Punjab’s agriculture through enhanced farm tools and mechanization. Key findings highlight inadequacies in research, manufacturing, and distribution of implements, along with labor shortages and fragmented landholdings. Recommendations include strengthening research and training, standardizing designs, promoting small-power mechanization, and expanding agricultural credit facilities. The report provides a detailed assessment of hand tools, seed drills, and threshers, demonstrating their potential to reduce labor, save time, and improve productivity. Emphasis is placed on practical demonstrations, cooperative production, and skill development to ensure effective adoption. By implementing these measures, Punjab can achieve higher efficiency, economic growth, and sustainable development in its agricultural sector.
Committee on Plan Projects (Agriculture Team) New Delhi August 1963
Keywords: Improved Agricultural Implements; Punjab Agriculture; Farm Mechanization; Hand Tools; Seed Drills; Threshers; Agricultural Productivity; Extension Work; Training Programs; Agricultural Credit